Character building through boarding school for inland and outermost student: a grounded theory approach - Sobon, Kosmas; Herwin,; Ohoitimur, Johanis; Sartono, E. Kus Eddy; Murdiono, Mukhamad (Frontiers in Education, 2025)
Many children who live in the interior and mountainous areas of Papua-Indonesia do not get the right of education. This research aims to formulate a theoretical concept of boarding school-based character education by implementing Papuan cultural contextual education in the process of education. The method used is a qualitative method with a grounded theory approach. The research participants were 14 people. Data were collected through semi-structured interviews and textual analysis of the interview results. The data analysis technique uses the Atlas.ti application by using three levels of coding: open coding, axial coding, and selective coding. The research results show that there are six main concepts as a model of boarding school character education: personal development, spiritual development, extracurricular activities, clean and healthy lifestyles, learning from inspirational figures, and academic development. These six theoretical concepts can be divided into internal and external character building. One of the uniqueness of character education is the integration of local cultural values in the whole process of character education of the children, both in the school environment and in the dormitory. The results of the study provide insights for educators, schools, and government on different forms of character education models.